Ethnopolitics among the Sámi in Scandinavia: A Basic Strategy toward Local Autonomy - Svensson, Tom G. (ARCTIC, 1986)
Communities in the far north face severe difficulties in trying to function as autonomous units due to the north-south axis in which northern resources are sought by southern industrial powers. Ethnopolitics as practiced by the Sámi in Scandinavia represent a political solution to those difficulties. For ethnopolitical processes to work to the advantage of the minority people, the communities must have a power base leading to local autonomy. Such autonomy is based typically on land and water rights. The entire ethnic minority is dependent on viable local communities leading to cultural pluralism, an effective defense against assimilation by the majority society. Cultural viability, firm land rights and institutionalized ethnopolitics provide the basis for strengthening local autonomies to such ends.Key words: Sàmi, ethnopolitics, local autonomy, land rights, cultural viability Mots clés: Sami, ethnopolitique, autonomie locale, droits territoriaux, viabilité culturelle